Metamaterial Sensing of Cyanobacteria Using THz Thermal Curve Analysis - Tae Hee Jeong; Seung Won Jun; Yeong Hwan Ahn (Biosensors)
In this study, we perform thermal curve analyses based on terahertz (THz) metamaterials for the label-free sensing of cyanobacteria. In the presence of bacterial films, significant frequency shifts occur at the metamaterial resonance, but these shifts become saturated at a certain thickness owing to the limited sensing volume of the metamaterial. The saturation value was used to determine the dielectric constants of various cyanobacteria, which are crucial for dielectric sensing. For label-free identification, we performed thermal curve analysis of THz metamaterials coated with cyanobacteria. The resonant frequency of the cyanobacteria-coated metasensor changed with temperature. The differential thermal curves (DTC) obtained from temperature-dependent resonance exhibited peaks unique to individual cyanobacteria, which helped identify individual species. Interestingly, despite being classified as Gram negative, cyanobacteria exhibit DTC profiles similar to those of Gram-positive bacteria, likely due to their unique extracellular structures. DTC analysis can reveal unique characteristics of various cyanobacteria that are not easily accessible by conventional approaches.